Um luminômetro Fluxo-Batelada para Determinação de Vitamina B12 em Medicamentos. - Andrade, Renato Allan Navarro (2011)
In this work was developed a luminometer for analysis by chemiluminescence, coupled to a flow-batch analysis automatic system. The performance of the developed instrument was evaluated by means of the determination of vitamin B12 in pharmaceutical formulations. The chemical principle is based on the catalytic effect of cobalt (II) ion over luminol oxidation by hydrogen peroxide in alkaline medium whose reaction product emits electromagnetic radiation in visible region (more precisely at 425 nm). The detection system of the developed instrument consisted of a silicon photodiode and a module for amplification of analytical signals. The univariate calibration model was validated by means of Analysis of Variance (ANOVA) and used later in the quantification of vitamin B12 in real samples. The limits of detection and quantification obtained were 0.11 and 0.36 μg L-1 of vitamin B12. The analytical frequency was estimated in 90 samples h-1. The accuracy of the proposed instrument was attested by means of recovery tests whose obtained recovery rates were between 98 and 102%. The proposed instrument yielded results with satisfactory precision, as revealed by low value of overall standard deviation. Such results demonstrated that is possible to quantify vitamin B12 employing a simple, economic and robust method which generate low amount of waste to the environment.